Multi-Hazard Analysis in Gunungkidul Regency Using Spatial Multi-Criteria Evaluation - Mustikaningrum, Melati; Widhatama, Adrianus Farrel; Widantara, Khrisna Wasista; Ibrohim, Mirza; Hibatullah, Muhammad Fikri; Larasati, Rinanda Amdalista Prastia; Utami, Sri; Hadmoko, Danang Sri (Forum Geografi, 2023)
This study has two aims: to determine the spatial distribution of multi-hazard levels and to discover the interactions, interdependencies, and effects that cascade among hazards in Gunungkidul Regency, Special Region of Yogyakarta. A multi-hazard map was created with a scale of 1:250,000 and modelled using SMCE (Spatial Multi-Criteria Evaluation). The conditioning factors used included slope, rainfall, historical data, river distance, geomorphology, land cover, lithology, and fault distance. The selected conditioning factors for each hazard were then weighted using weighted overlay analysis. The results showed that the area of Gunungkidul can be included in the high-risk category for floods, since the probability of flooding is 56.72%, the probability of landslides is 9.14%, that of drought is 48.86%, and that of seismic disturbance is 20.83%. (Multi-hazard maps are created by overlaying flood, landslide, seismic, and drought hazard maps.) After these risk factors were calculated, the regions on the multi-hazard map were re-categorized into five hazard classes. All areas in Gunungkidul Regency have multiple hazards, with risk factors of different magnitudes. The interaction between hazards can generate new hazards that are called cascading hazards. The cascading hazards in the study area are most likely to occur in the north of Gunungkidul Regency with its very high seismic and landslide hazard risk factors, due to the geological and geomorphological conditions of the Baturagung Structural Hills.